Performance evaluation of integrated resilience engineering factors by data envelopment analysis: The case of a petrochemical plant - Azadeh, A.; Salehi, V.; Ashjari, B.; Saberi, Morteza (Elsevier, 2014)
Petrochemical units are potentially prone to incidents that have catastrophic consequences such as explosion, leakage of toxic materials, and the stoppage of the production process. Resilience engineering (RE) is a new method that can control incidents and limit their consequences. It includes top-level commitment, reporting culture, learning, awareness, preparedness, and flexibility. However, this study introduces a new concept of RE (referred to as integrated RE or IRE) which includes the above factors in addition to self-organization, teamwork, redundancy and fault-tolerant. This study evaluates performance of IRE in a petrochemical plant through considering the obtained data from questionnaires and data envelopment analysis (DEA) approach. Moreover, the performance of RE and the new IRE are compared and discussed. The results show that although there is a strong direct correlation between the DEA results in two frameworks, the mean scores of efficiency in IRE is slightly higher than RE. This is the first study that introduces an integrated approach for RE. In addition, this study is amongst the first ones that examine the behavior of resilience engineering by DEA. Moreover, the superiority of IRE is shown through robust statistical analysis.